IMPLICATIONS OF ELECTRIC VEHICLES USE ON VALUE CO-CREATION AND IMPROVING COMMUNITY WELFARE - Hanum, Rastinia Kamila; Halim, Rizal Edy (Journal of Environmental Science and Sustainable Development, 2025)
Transportation is closely related and to support daily community mobility, 90% of road transportation operates on fossil fuel and it has always been accompanied by new innovations. Electric vehicles are predicted to be the future transportation to reduce greenhouse emissions. This study combines theories on behavioral and technology acceptance to create value co-creation and enhance community well-being. This quantitative study surveyed 210 respondents from the target community especially in Java island, who intend to adopt electric vehicles (EVs) using Google Form. PLS-SEM was used to evaluate research framework which integrates TPB, Technology Acceptance Model (TAM), and Unified Theory of Acceptance and Use of Technology (UTAUT) with value co-creation and quality of society life into nine hypotheses. The study results showed that perceptions of technology security, technology trust, community empowerment, and subsidy policies have a significant effect on adoption intentions (p-value0.05). Adoption intention did not significantly affect on the quality of life (p-value 0.142>0.05). Intention to adopt, value co-creation, and subsidy policy have a positive relationship with the quality of community life. The government's roles in ensuring consistent subsidy policies and community empowerment program is crucial for building awareness and trust to adopt the EV.